2018
DOI: 10.24171/j.phrp.2018.9.4.07
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Smoking Cessation Intervention Education Program Based on Blended Learning among Nursing Students in South Korea

Abstract: ObjectivesThis study was conducted to evaluate whether a “smoking cessation intervention” education program based on blended learning, was effective in improving nursing students’ perceived competence and motivation to perform a smoking cessation intervention for smokers.MethodsA quasi-experimental, pretest–posttest design was conducted. The smoking cessation intervention education program based on blended learning, was administered to the experimental group (n = 23) in 5 sessions, consisting of 2 courses of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 19 publications
1
20
0
Order By: Relevance
“…This study suggests that the inclusion of tobacco cessation education, directed by the Guidelines 5 and the Manual 23 , into nursing compulsory courses, in the form of a classroom didactic session, online selflearning, and a scenario simulation session, effectively increased nursing students’ knowledge, skills, and confidence in tobacco cessation, which was consistent with the results of previous studies1 6 – 19 . This study also found that students performed skills learned in the course to actively assist patients to quit smoking.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…This study suggests that the inclusion of tobacco cessation education, directed by the Guidelines 5 and the Manual 23 , into nursing compulsory courses, in the form of a classroom didactic session, online selflearning, and a scenario simulation session, effectively increased nursing students’ knowledge, skills, and confidence in tobacco cessation, which was consistent with the results of previous studies1 6 – 19 . This study also found that students performed skills learned in the course to actively assist patients to quit smoking.…”
Section: Discussionsupporting
confidence: 89%
“…The tobacco cessation education achieved relatively good results, probably because of the traditional didactic session with specific instruction on tobacco cessation health education theories such as the transtheoretical model of behavior change 25 , the 5As and 5Rs theoretical models of tobacco cessation, and the provision of the corresponding online resources. Those online resources were about different cases with assistance from different medical professionals, which were easily accessible and could be repeatedly learned 17 19 . The online Q and A helped students to solve problems in self-learning.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, an experimental study conducted by Sung, Kwon, and Ryu (2008) revealed that blended groups had a higher statistically significant level of knowledge and satisfaction related to administration of medication skills and knowledge compared with the control group, while there were no statistically significant differences between the groups in relation to self‐efficacy. Choi and Kim (2018) conducted a quasi‐experimental design to evaluate the effectiveness of an educational programme related to smoking cessation based on blended learning in improving nursing students' competence and motivation to conduct a smoking cessation intervention for smokers. The results showed that the educational programme adopting blended learning was significantly effective in developing nursing students' competences and motivation in conducting a successful programme.…”
Section: Discussionmentioning
confidence: 99%